Effect of the GLP-1 receptor agonist semaglutide on metabolic disturbances in clozapine-treated or olanzapine-treated patients with a schizophrenia spectrum disorder: study protocol of a placebo-controlled, randomised clinical trial (SemaPsychiatry) - Jimmi Nielsen; Christoph U Correll; Tina Vilsbøll; Maj Vinberg; Claus Ekstrøm; Anders Fink-Jensen; Heidi Storgaard; Filip K Knop; Ole Mors; Marie Reeberg Sass; Andreas Aalkjær Danielsen; Ole Köhler-Forsberg; et al. (BMJ Open, 2023)
Introduction Clozapine and olanzapine are some of the most effective antipsychotics, but both are associated with weight gain and relevant metabolic disturbances, including pre-diabetes and diabetes. Non-pharmacological/behavioural interventions have had limited effects counteracting these adverse effects. Semaglutide, a glucagon-like peptide 1 receptor agonist, is approved for the treatment of type 2 diabetes and obesity. We will investigate the long-term effects of add-on treatment with semaglutide once a week versus placebo once a week on the metabolic status in pre-diabetic (glycated haemoglobin A1c (HbA1c) 35–47 mmol/mol (5.4%–6.4%) and diabetic (HbA1c 48–57 mmol/mol (6.5%–7.4%)) patients diagnosed with a schizophrenia spectrum disorder who initiated clozapine or olanzapine treatment within the last 60 months.Methods and analysis This is a 26-week, double-blinded, randomised, placebo-controlled trial. Altogether, 104 patients diagnosed with a schizophrenia spectrum disorder, aged 18–65 years, with pre-diabetes or diabetes will be randomised to injections of 1.0 mg semaglutide once a week or placebo for 26 weeks. The primary endpoint is change from baseline in HbA1c. Secondary endpoints include changes in body weight, hip and waist circumference and plasma levels of insulin, glucagon, glucose, and C-peptide, insulin sensitivity, beta cell function, hepatic function, fibrosis-4 score, lipid profile, incretin hormones, bone markers, body composition, bone density, proteomic analyses and oxidative stress markers. Together with alcohol, tobacco and drug use, potential effects on the reward value of a sweet–fat stimulus, psychopathology, level of activity and quality of life will also be assessed.Ethics and dissemination This study is approved by the Danish Medicines Agency and the regional scientific ethics committee of the Capital Region of Denmark (committee C, #H-20019008) and will be carried out in accordance with International Council for Harmonisation Good Clinical Practice guidelines and the Helsinki Declaration. The results will be disseminated through peer-review publications and conference presentations.Trial registration number NCT04892199.